Effect of Self-Assessment Against Identify Learning Needs and Nursing Student Learning Activities Polytechnic Kemenkes Palangkaraya - Maria Magdalena Purba; Ester Inung Sylvia; Alfeus Manuntung (Pusat Penelitian dan Pengabdian kepada Masyarakat, Poltekkes Kemenkes Semarang, 2013)
Background: Health professionals especially nursing is demanded to always has given best well-being service for individual family and society. Self-assessment is important in course of up to how does nursing education can to develop ability self-assessment. In course of education, Self-assessment look at tool to identify learning needs, detecting strength and weakness so that student university can to determine which competence that must be studied well. Aim: The aim of the research is to detects influence self-assessment in course of nursing student’s learning at Poltekes kemenkes palangka Raya, particulary in setting learning need priority promoting learning activity. Methods: This research is quantitative used quasi experiment non-randomized control group pretest-posttest design. Respondents of research were nursing students of Poltekes Kemenkes Palangka Raya, regular class XIVA with total 38 respondents as a group controls and regular class XIVB with total 38 respondens as interventions groups Result: Analysis based value student’s learning needs perception intervention group shows increase learning need perception, Where does intervention group learn more deepen in certain aspects in vital marking measurement with statistics value p = 0, 047, analysis based on method learns that used for this know-how achievement 97% autodidact method Conclusion: Analysis result shows that training self-assessement influential towards aspects in prioritise student’s learning need and learning activity.